1994
DOI: 10.1021/ma00104a021
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular Assembly between Nanoparticles of Hydrophobized Polysaccharide and Soluble Protein Complexation between the Self-Aggregate of Cholesterol-Bearing Pullulan and .alpha.-Chymotrypsin

Abstract: Complexation between -chymotrypsin (Chy) and the self-aggregate of cholesterol-bearing pullulan (CHP) was studied by size exclusion column chromatography (SEC), fluorescence spectroscopy, circular dichroism (CD), and differential scanning calorimetry (DSC). The CHP self-aggregate strongly complexed with the Chy dimer and formed colloidally stable nanoparticles (Re = 12 nm) at pH 4.2 and 25 °C. Enzymatic degradation of the CHP-Chy complex by pullulanase suggested that Chy may locate deeply inside the matrix of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
104
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 169 publications
(104 citation statements)
references
References 5 publications
0
104
0
Order By: Relevance
“…Especially, the hydrophobic interaction between the hydrophobic domain and the hydrophobic surface of insulin exposed by part denaturation is very important, and is the main driving force for the denaturation of the insulin-FITC native structure. 19,24,[29][30][31][32] Possibly due to part denaturation, it was observed that the hydrophilic insulin-FITC molecules immediately became precipitate, when adding peptide RATEA16 into its aqueous solution (see Supporting Information). At the same time, the extent to b-sheet secondary structure of peptide increased, indicating that the existence of insulin-FITC molecules redounded to the b-sheet formation of peptide RATEA16.…”
Section: Drug Loadingmentioning
confidence: 99%
“…Especially, the hydrophobic interaction between the hydrophobic domain and the hydrophobic surface of insulin exposed by part denaturation is very important, and is the main driving force for the denaturation of the insulin-FITC native structure. 19,24,[29][30][31][32] Possibly due to part denaturation, it was observed that the hydrophilic insulin-FITC molecules immediately became precipitate, when adding peptide RATEA16 into its aqueous solution (see Supporting Information). At the same time, the extent to b-sheet secondary structure of peptide increased, indicating that the existence of insulin-FITC molecules redounded to the b-sheet formation of peptide RATEA16.…”
Section: Drug Loadingmentioning
confidence: 99%
“…CHP can form stable hydrogel NPs by self-assembly, 13,14 and can then form complexes with various drugs and proteins by hydrophobic interaction and release them upon exposure to specific proteins or cyclodextrin. [15][16][17][18] The hydrogel NPs can also be used as a drug carrier system in medicine 17,19,20 as well as artificial molecular chaperones in biotechnology. [21][22][23] On the basis of these, our group developed a new method to synthesize cholesterol-modified pullulan (CHSP) by directly grafting proper cholesterol residues onto pullulan using succinyl linkages, thus providing a new strategy for the effective and safe synthesis of CHSP.…”
Section: Introductionmentioning
confidence: 99%
“…15 Cholesterol is often used to modify biomaterials hydrophobically due to its rigid and highly hydrophobic sterol skeleton. 16,17 The two main goals of the present work were, firstly, to report a novel amphiphilic copolymer, ie, FA-PEG-PCHL, with a series of molecular weights (4374-12394 Da) and low cytotoxicity, and, secondly, to investigate the characteristics, in vitro cytotoxicity, intracellular uptake, apoptotic effect, in vivo pharmacokinetics, and tissue distribution of FA-PEG-PCHL-modified, freeze-dried docetaxel-loaded liposomes (FA-PDCT-L).…”
Section: Introductionmentioning
confidence: 99%